FLAMENCO AS A HERITAGE CULTURAL OR CONSTRUCTION MORE ARTIFICIAL OF THE IDENTITY ANDALUZA - Steingress, Gerhard (ANDULI, Social Sciences Journal, 2003)
Being far from a simple artistic and folkloristic expression, the symbolic significance of flamenco within the context of the Andalusian culture has increased during the last two decades as a consequence of the diversification of the artistic field in the era of globalization and the influence of revalorization of the local and the autochthonous. This article discusses some of the main arguments and their implications in the present politics of patrimonialization of flamenco from a critical point of view and based on the dialectics of cultural essentialism and artistic vanguardism.